Examining the relationship between the creativity levels of the classroom environment and the preschool children - Züleyha Yuvacı (Erken Çocukluk Çalışmaları Dergisi, 2018)
The aim of this study was to investigate the relationship between the creative classroom environments and the creative thinking skills of six-year old children in three central districts (Melikgazi, Kocasinan and Talas) of Kayseri province in Turkey. The participants of the study included 51 teachers and 357 students in their classes. The teachers who participated in this study were administered “the Pre-school Creative Classroom Environment Scale” for their perception of the level of creativity in their classes and the children were administered “the Integrated Creativity Test” to determine their level of creativity. The results of the research revealed that these children have a medium level creativity while the teachers’ perception of the classroom environment for creativity was quite high. This discrepancy can be attributed to the teachers’ tendency to evaluate their own classroom environments more positively for creativity. Still, a positive but low-level relationship was found between the creativity levels of the pre-school classroom environments and the creativity levels of the children. This finding suggests that teachers cannot always organize creative classroom environments in line with preschoolers’ interests, abilities, skills and needs, or cannot organize activities that lead to children’s use of their creativity in the classroom setting.